Life Problems Facing Horticultural crops and Strategies of Facing them in Maysan Governorate - Radi Abbas Al-Maliki , Maryam; Abadi Hammadi Jassim , Assist.Prof. Dr. Kazem (Basra studies journal, 2022)
A group of life factors participate in crystallizing many problems that stand in the way of development of horticultural crops in Maysan Governorate, these were represented by (agricultural diseases and pests), so this study came to clarify life problems facing the cultivation of horticultural crops and the most important ways and strategies to develop them and achieve sustainable agricultural development for them in Governorate of Maysan.